Kulturalistična ideologija v literarni teoriji - Habjan, Jernej (Primerjalna književnost, 2012)
The age-old gap between humanities and sciences is being cynically bridged by the neoliberal subjection of both humanist and scientific theory to expert knowledge, in the humanities mostly to cultural studies, a key source of which is the conception of performativity. The article sketches the process leading from Austin's proto-theoretical "nomothetic" exclusion of literature from his theory of the performative to Butler's ideological "idiographic" grounding of her conception of performativity in literature.
Keywords: literarna teorija; literary theory; teorija govornih dejanj; performativnost; kulturni študiji; ideologija; neoliberalizem